ENHANCING ELEMENTARY STUDENT ACHIEVEMENT THROUGH THE MAKE A MATCH MODEL: CASE STUDY AT SD NEGERI SELANGIT - Dafis (CV Grasta Glory, 2025)
This research aims to explore the implementation of the Make a Match learning model in improving student learning outcomes in elementary school education. The study was carried out at SD Negeri Selangit using classroom action research (CAR) consisting of two cycles. The research subjects were 28 fourth-grade students during the 2024/2025 academic year. Each cycle consisted of four stages: planning, action, observation, and reflection. Data were collected through tests, observation sheets, documentation, and field notes. The initial average score before the intervention was 64.50, with a learning completeness of only 46%. After the implementation of the Make a Match model, the average score improved to 72.14 in the first cycle and 84.67 in the second cycle. Completeness also increased to 67% in Cycle I and 89% in Cycle II. The Make a Match learning model encouraged student collaboration, increased enthusiasm for learning, and enhanced retention of subject matter. These findings suggest that the Make a Match model is a practical approach for improving student learning outcomes at the elementary level. Furthermore, it is recommended that future research apply this model to other grade levels and subject areas, explore its integration with digital tools, and evaluate its long-term impact on students’ critical thinking and collaboration skills.